Peran Sistem pengendalian Internal, Sistem Informasi Akuntansi, dan Literasi Pengelolaan Keuangan dalam Mencegah Fraud Pada Koperasi di Jakarta Utara - Fangela Myas Sari; Sunarto Sunarto (Akbis: Media Riset Akuntansi dan Bisnis, 2026)
This study examines the role of Internal Control Systems (ICS), Accounting Information Systems (AIS), and financial management literacy in preventing fraudulent practices within cooperatives in North Jakarta. A qualitative descriptive approach was 12 employed, with data collected through in-depth interviews, direct observations, and document analysis involving several active cooperatives. The findings reveal that consistent implementation of internal control mechanisms, particularly functional segregation and layered authorization procedures, plays a crucial role in reducing opportunities for fraud. Furthermore, the adoption of digital-based accounting information systems enhances transparency by providing reliable audit trails, thereby limiting the potential for data manipulation. In addition, the financial management literacy of cooperative administrators functions as an early warning mechanism in identifying irregular financial activities. Overall, the study highlights that the integration of robust control systems, effective information technology, and competent human resources is essential for establishing a comprehensive fraud prevention framework within cooperative organizations.